Infantile Alexander Disease: Case Report and Review of Literature - Soumyabrata Sarkar; Rupam Sinha; Amitabha Chakraborty; Tanya Khaitan; Biyas Bhowmik (Journal of Clinical and Diagnostic Research, 2017)
Alexander Disease (AD) is an autosomal dominant leukodystrophy and occurs predominantly in infants and children. It usually results in death within ten years after onset. Among the four subtypes, infantile form comprises the most of affected individuals. It presents in the first two years of life, typically with progressive psychomotor deficiency, loss of developmental milestones, seizures, and pyramidal signs. Clinical and magnetic resonance image findings usually establish diagnosis of AD. Here, we present a case of Infantile AD with characteristic clinical and radiological features.